Папілярний рак щитоподібної залози із кістозними змінами: клініко-морфологічні особливості - Ларін, О. С.; Хоперія, В. Г.; Гузь, О. О.; Кротевич, М. В. (Clinical Endocrinology and Endocrine Surgery, 2009)
We reviewed the records of 68 patients who underwent thyroidectomy for the cancer between 2006 and 2008 including their clinical data, type and size of thyroid nodule, FNA cytology results, and final pathology report of the surgical specimen. Most of the thyroid cysts in patients with carcinoma measured 2 to 4 cm in diameter. Results suggested that the incidence of metastasis higher in 2,6 times in patients with cystic papillary carcinoma. Data obtained may be useful in proper management of this pathology.